Standardized catch ratesin number of fish by age for the North Atlantic swordfish (Xiphias gladius) of the Spanish longline fleet, for the period 1983-2011 - Mejuto-García, Jaime; García-Cortés, Blanca; Ramos-Cartelle, Ana (2023)
No